Application of the defect management improvement mode under Joint Commission International standard to improve the instrument cleaning and disinfection effect and management quality in the central sterile supply department: a randomized trial - Yang, Lingyun; Xun, Qin; Xu, Jie; Hua, Da (Annals of translational medicine, 2022)
Professional, standardized, and scientific management of the disinfection supply room is the prerequisite to ensure medical quality and improve the comprehensive strength of the hospital. This study aimed to evaluate the application of the defect management improvement mode of the Joint Commission International (JCI) standard in improving the cleaning and disinfection effect as well as the management quality of instruments in the central sterile supply department (CSSD). From January 2020 to December 2020, 32 medical staff in the hospital CSSD were divided into control and observation groups according to the random number table method, with 16 staff members in each group. The control group adopted the standardized management mode and the observation group adopted the defect management improvement mode based on the JCI standard. During the management period, we compared the disinfection effect and incidence of adverse events of the instruments and articles in the CSSD of the two groups, and evaluated the work and satisfaction of both groups of subjects. Linear correlation analysis and multiple linear regression analysis were used to determine the influencing factors of satisfaction. During the standardized management, the instruments and articles were used 611 times in the control group and 602 times in the observation group. The cleaning qualified rate, infection awareness rate, standard implementation rate, hand hygiene implementation rate, theoretical knowledge score, and practical operation ability of the observation group were significantly higher than those of the control group (P<0.05). The incidence of adverse events in the observation group was significantly lower compared to the control group (P<0.05), and the satisfaction scores of the observation group were significantly higher than those of the control group (P<0.05). The total satisfaction score is independently related to the training method, educational background, and professional title. Adopting the defect management improvement mode under the JCI standard for CSSD is conducive to improving the cleaning effect of instruments, enhancing the work situation and job satisfaction of medical staff, and reducing the incidence of adverse events. Chinese Clinical Trial Registry ChiCTR2100053068.